2023
DOI: 10.17219/acem/157240
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for predicting skip metastasis in cN0 papillary thyroid cancer patients at increased risk of lymph node metastasis

Abstract: Background. Skip lymph node metastasis (SLNM) refers to lateral lymph node metastasis (LLNM) without involving central lymph node (CLN). Some microscopic nodal positivity may be difficult to detect before surgery due to atypical imaging characteristics. These patients are misdiagnosed as having clinically nodenegative (cN0) papillary thyroid cancer (PTC) even after central lymph node dissection, leading to a high risk of developing LNM after surgery. Current prediction models have limited clinical utility, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The tumor invades the adjacent neck lymph nodes through blood vessels and lymphatic vessels, and even distant metastasis occurs ( 25 ). According to the previous studies ( 17 , 26 ), capsule invasion was also considered as a predictive factor of skip metastasis in PTC patients. In addition, the upper pole of thyroid tissue is relatively thin due to the butterfly shape of the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor invades the adjacent neck lymph nodes through blood vessels and lymphatic vessels, and even distant metastasis occurs ( 25 ). According to the previous studies ( 17 , 26 ), capsule invasion was also considered as a predictive factor of skip metastasis in PTC patients. In addition, the upper pole of thyroid tissue is relatively thin due to the butterfly shape of the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how these pathways regulate these processes in the context of TLR3 activation could provide insights into the complex roles TLR3 plays in breast cancer progression and tumor microenvironment modulation. Tumor cells exhibiting high TLR3 expression correlate with a higher likelihood of metastasis ( 30 ). Studies have reported elevated TLR3 expression in breast cancer cells compared to normal cells, with TLR3 activation linked to increased cell proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) in vitro , as well as enhanced tumor growth and metastasis in mouse xenograft models ( 60 ).…”
Section: Toll-like Receptors In Breast Cancermentioning
confidence: 99%
“…Papillary thyroid carcinoma that is located in the isthmus exhibits aggressiveness and is related to poor prognosis. A nomogram including incriminated factors for metastatic lymph nodes and worse outcome (gender, age, size of malignant lesion, thyroid cap invasion, and Hashimoto’s thyroiditis)[ 75 ], as for any other location of high-risk patients[ 76 ], predicts recurrence[ 77 ].…”
Section: Pre/postoperative Prediction Factors-recurrencementioning
confidence: 99%